Сибирская амазонка: [роман] / Ирина Мельникова - Мельникова Ирина Александровна (Незнакомка, 2011)
Экземпляры: ф.6 (20161201) / Инвентарный номер: 48675 / Цена: 70.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М 48 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-4